Représentations sociales et significations des pratiques écologiques : Perspectives de recherche - Sabine Caillaud (VertigO, 2010)
The aim of this article is to propose some new research’s lines to understand the senses accorded to ecological practices by paying attention to social representations of pollution. First we present some studies about the link between attitudes and behavior toward ecology and some of their limits. Then, we propose to use another approach : the social representations one, in order to take into account common sense knowledge about ecology. This approach should allow us to understand the sense people give to ecological individual practices. Some elements about the social cultural context of this study give some responses to the question and lead to the bases of our methodology : the opposition between ecology and economy, modernity and the ecological shortage... Focus groups were conducted with French students. Dilemmas were presented in which the pollution varied between local and global. Our results bring some evidences for dichotomies (visible/invisible, rich/poor) which structure the social representations of pollution. These dichotomies enlighten different senses of ecological practices. Moreover our results show that the way nature and humans relations are perceived is based on an anthropocentric or an ecocentric view depending on pollution’s characteristics (local/global).